Evaluation of the possible effect of Ursodeoxycholic Acid to treat rheumatoid arthritis induced in the Rat model in comparison with Diclofenac. - Yamama Raad; Ahmed Hamed Jwaid (College of Pharmacy University of Baghdad, 2024)
Background: It is well known that ursodeoxycholic acid (UDCA) has notable impacts on the liver, However, tiny amount of knowledge available on how it affects autoimmune illness. This research was done to see an advantage that might exist of using UDCA in Rheumatoid arthritis (RA). Methods: In order to accomplish this objective, adult either sex rats were divided  into 4 groups: Normal control (sodium bicarbonate 5% p.o. for 21 days),CFA (0.1 ml CFA footpad intradermal injection),FCA+ Diclofenac (5 mg/kg p.o for 21 days),FCA+ UDCA (100 mg/kg p.o. for 21 days). Results: UDCA (100 mg/kg p.o.) show significantly a rise in Body Mass also significantly  reduce in Arthritic Oedema score in comparison with induction group . RBC, WBC, and ESR were Hematological UDCA therapy of animals Evaluation findings  RBC increased noticeably and WBC ,ESR levels drop noticeably. a considerable drop in TNFα and RF biochemical parameters evaluated in UDCA treatment group. Keywords: rheumatoid arthritis (RA); ursodeoxycholic acid (UDCA) and Complete Freund adjuvant (CFA)